A FEW OF TURBIDITE CHARACTERISTIC FEATURE IN THE VICINITY OF BANTARUJEG - -, Abdurrokhim (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
The traversing of Cilutung River exposes the sedimentary rock which is corresponding to turbidity system sedimentation. In around Bantarujeg area, the composite lithology is characterized by monotonous of poorly sorted tuffaceous sandstone interbedded with mudstone of classical turbidite; coarse grain of pebbly sandstone; interbedded tuffaceous sandstone and mudstone of slump deposits; disorganized pebble-coble-sized components of mud supported; massive sandstone and polymix breccia. A genetic unit based on sedimentary processes is more reliable in order to grouping the lithostratigraphic units.